2005
DOI: 10.1208/aapsj070368
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of mono- and bis-quaternary ammonium salts as ligands at the α4β2 nicotinic acetylcholine receptor subtype using nonlinear techniques

Abstract: The neuronal nicotinic acetylcholine receptor (nAChR) has been a target for drug development studies for over a decade. A series of mono- and bis-quaternary ammonium salts, known to be antagonists at nAChRs, were separated into 3 structural classes and evaluated using both self-organizing map (SOM) and genetic functional approximation (GFA) algorithm models. Descriptors from these compounds were used to create several nonlinear quantitative structure-activity relationships (QSARs). The SOM methodology was effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…GFA has been used by other researchers as well to develop good QSAR models. 19,20) The goodness of the regression fits are estimated using parameters such as, r 2 (ϭ1ϪSSE/TSS), r 1Ϫr 2 )) and MSSE (ϭmean sum of square of errorϭSSE/n) where, TSSϭtotal sum of squares and SSEϭsum of squares, PRESSϭpredicted sum of squares based on leaveone-out method.…”
Section: Methodsmentioning
confidence: 99%
“…GFA has been used by other researchers as well to develop good QSAR models. 19,20) The goodness of the regression fits are estimated using parameters such as, r 2 (ϭ1ϪSSE/TSS), r 1Ϫr 2 )) and MSSE (ϭmean sum of square of errorϭSSE/n) where, TSSϭtotal sum of squares and SSEϭsum of squares, PRESSϭpredicted sum of squares based on leaveone-out method.…”
Section: Methodsmentioning
confidence: 99%
“…3D QSAR and QSAR studies on nAChR paralleled the efforts in the development of the pharmacophore models, [95,189,190,193,[195][196][197][198] supporting the rational design and synthesis of novel nicotinic ligands. [60,71,95] The pharmacophoric patterns of nAChR, both from SAR and computational techniques such as DISCO and Catalyst HipHop, were widely used in the conformer selection and in the alignment of the ligands involved in the development of the nicotinic 3D QSAR models, that is, in the construction of mathematical models aimed at uncovering relationships between chemical properties, the 3D molecular features of the compounds, and biological activity of the set of nicotinic ligands.…”
Section: Allosteric Modulatorsmentioning
confidence: 99%
“…Two recent reviews that report on ligand-based models of neuronal nAChR agonists, involving either pharmacophore development or quantitative structure-affinity relationships, have been reported by Glennon et al and Nicolotti et al, respectively [29-30] More recently, QSAR studies in this area that focus on specific types of analogs, have also been reported [31-35]. With regard to quaternary ammonium nAChR antagonists, QSAR studies on a series of mono - and bis -quaternary ammonium salts have been reported by Ayers et al [36]. In this study, the Self Organizing Maps (SOM) approach was used to classify the compounds according to their structures and activities.…”
Section: Resultsmentioning
confidence: 99%